Особливості містобудівних вирішень та еволюції поселень для переселенців з чорнобильської зони - Гнесь, Людмила; Hnes, Liudmyla (Видавництво Львівської політехніки, 2021)
Репрезентуються результати власних натурних досліджень еволюції поселень для переселенців із Чорнобильської зони, зведених в 1986–1987 роках ХХ ст. Розглядаються стратегії та наслідки їхнього розміщення, інтеграції в структуру існуючих сіл, особливості розпланування кварталів, сільських садиб, житлових і господарських будівель. Аналізуються наслідки прийнятих архітектурно-містобудівних проектних рішень через 30 років після їхньої реалізації.

In the article, the author presents the results of her full-scale studies of the evolution of settlements for migrants from the Chernobyl zone, built in 1986–1987 of the twentieth century. Strategies and consequences of their placement, integration into the structure of existing villages, features of planning blocks, rural estates, residential and outbuildings are considered. The article analyzes the consequences of architectural and urban planning design decisions made 30 years after their implementation. Nowadays in Ukraine, there is a situation where villages and urban-type settlements urgently need to develop or update new general plans that would correspond to the present. It is known that currently there is a certain proportion of villages in Ukraine that do not have general plans at all or have them outdated. Taking into account all aspects of this problem, the results of the design, construction and evolution of villages for displaced persons from the Chernobyl zone are interesting and useful. Taking into account the tragic circumstances that led to their appearance, these villages represent a large-scale urban planning experiment in the field of rural housing construction, which represents the embodiment of the latest knowledge in the theory of village architecture in the mid-80s of the twentieth century. It was 30 years after the construction and settlement of these villages that it became possible to check the compliance of design standards with their compliance with the real needs of the village, from the standpoint of the current design standards, which are fundamentally no different from the design standards of 1986. Comparing the results of research (the study of general plans of villages of displaced persons and general plans that are being developed at the present stage), it turned out that the basis of those villages for Chernobyl victims was the main goal of socialist ideology, namely, erasing the differences between the city and the village. The author sees in modern design a similar problem, which directly leads to further degradation of the Ukrainian countryside. And nowadays, just against the background of this phenomenon, it is time for urbanists to understand the difference between a block of manor development for citizens and a rural street of a Ukrainian village.
Features of urban planning solutions and the evolution of settlements for displaced persons from the chernobyl zone
Keywords: село; генплан; садиба; домогосподарство; подвір’я; будинок; господарські будівлі; сільськогосподарське виробництво; сельбищні території; площа; village; general plan; manor; household; farmstead; house; outbuildings; agricultural production; residential areas; area; 711. 4-122